Adaptive sequential plan-on-plan optimization during prostate-specific antigen response guided radiotherapy of recurrent prostate cancer. (April 2021) - Jóhannesson, Vilberg; Wieslander, Elinore; Nilsson, Per; Brun, Eva; Bitzén, Ulrika; Ahlgren, Göran; Olsson, Tomas; Bäck, Sven; Kjellén, Elisabeth; Gunnlaugsson, Adalsteinn
Abstract: Background: Treatment adaptation based on tumour biomarker response during radiotherapy of prostate cancer, could be used for both escalation and de-escalation of radiation doses and volumes. To execute an adaptation involving extension of treatment volumes during radiation can however be restricted by the doses already delivered. The aim of this work was to develop a treatment planning method that addresses this challenge. Material and methods: A volumetric-modulated-arc-therapy (VMAT) planning method with sequential plan-on-plan optimization was developed for a prospective phase II trial including 100 patients on salvage radiotherapy (SRT) for prostate cancer recurrence. A treatment adaptation was performed after five weeks of SRT based on prostate-specific antigen response during this phase of the treatment. This involved extension of treatment volumes for non-responders (n = 64) to include pelvic lymph nodes and boost to 68 Gallium-Prostate-Specific-Membrane-Antigen-Positron-Emission-Tomography positive lesions. This method was evolved by introducing an EQD2 (equivalent dose in 2.0 Gy fractions) correction of the base plan for improved dose coverage. Results: All dose-volume criteria for target coverage were met for the non-responders when based on physical dose. An EQD2 correction of the base plan for non-responders, implemented for the final 29 patients, led to a statistically significant improvement in dose coverage as compared to the 35 patients treated without EQD2 correction. Conclusions: This is to our knowledge the only study presented on biomarker-guided sequential VMAT radiotherapy using a plan-on-plan technique in the pelvis. By using a biologically adapted technique an improved target coverage was achieved without compromising doses to organs at risk.